On the Estimation of Standard Deviations in Multibeam Soundings - Eeg, Jorgen (The International Hydrographic Review, 2015)
This paper describes a simple and robust method of estimating the standard deviation of multibeam soundings. As an illustration of the method, upper and lower estimates of the standard deviations for the angular sector 0 to 60 degrees of the BCC (ELAC’s BOTTOMCHART COMPACT SHALLOW WATER) and RESON’s SeaBat-9001 system are calculated at various depths. Furthermore, the accuracy of the method is discussed, together with the case where the variation of the sea bed inside the footprint of the transducer beams cannot be ignored, the case in point being measurement of the size of a field stone situated at a depth of 22 metres.